“The pain of the innocent”: The suffering of non-humans and legal grounds against human cruelty - Ramos-Curo, Luz Tabitha (2026)
Animal abuse is a problem that affects a wide variety of species of living beings throughout the world. Mistreatment is defined as a set of actions that cause unnecessary harm and pain to the animal, resulting in its suffering or death. The objective of this article is to analyze the root causes of the suffering of non-human beings and to present the legal bases against human cruelty and to inform the general public about what these beings go through, which unfortunately do not have a voice to be heard, being the main scenario the department of Madre de Dios. Finally, the study stresses the responsibility and authority that must be exercised to help with the eradication of this problem and thus protect the life and health of animals, given that the premise is: to be the voice of those who do not have a voice.